2000
DOI: 10.1093/ndt/15.7.1098
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine in the treatment of renal amyloidosis secondary to familial Mediterranean fever

Abstract: We have read with interest the Letter to the Editor by Simsek Bulos N, Shahin HM. Familial Mediterranean fever in children: and colleagues [1] reporting the efficacy of colchicine in a the expanded clinical profile. QJM e d1999; 92: 309-318 nephrotic paediatric patient with amyloidosis due to familial 6. Sarkissian A, Papazian M, Sanamiam A, Babloyan A. Does Mediterranean fever (FMF ) with resolution of proteinuria. colchicine alter the course of amyloidosis in children with familial Mediterranean fever?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Many studies emphasized that, early initiation and absolute compliance with colchicine therapy are the most important approaches for regression in preservation of proteinuria in FMF-associated amyloidosis patients. 4,[8][9][10][11][12] The most beneficial effect of early initiation of colchicine therapy on decreasing proteinuria in pediatric amyloidosis patients is also consistent with these results 2,13 Additionally, our study revealed that, response to colchicine treatment should also depend on the etiology of amyloidosis. In the subgroup analysis, the amyloidosis was related with FMF in all of the responder to colchicine treatment.…”
Section: Discussionsupporting
confidence: 84%
“…Many studies emphasized that, early initiation and absolute compliance with colchicine therapy are the most important approaches for regression in preservation of proteinuria in FMF-associated amyloidosis patients. 4,[8][9][10][11][12] The most beneficial effect of early initiation of colchicine therapy on decreasing proteinuria in pediatric amyloidosis patients is also consistent with these results 2,13 Additionally, our study revealed that, response to colchicine treatment should also depend on the etiology of amyloidosis. In the subgroup analysis, the amyloidosis was related with FMF in all of the responder to colchicine treatment.…”
Section: Discussionsupporting
confidence: 84%
“…However, even with established amyloidosis some nephrotic patients may go into partial or even full remission after administration of colchicine, but the response is not predictable [18]. As compared to the first period, there was a slight decline in the second period (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) and it is expected that the number of renal amyloidosis will considerably decrease over the next years.…”
Section: Discussionmentioning
confidence: 99%
“…Livneh et al and Sarkissian et al [11,12] also reported on reversal of nephrotic syndrome in amyloidosis of FMF, suggesting that treatment with colchicine should be started as early as possible in the course of FMF and should be continued indefinitely at the highest possible dose. For the presented case, further follow-up and evaluation are needed for a possible favorable outcome with colchicine treatment in the future.…”
Section: Discussionmentioning
confidence: 99%